Efficacy and Safety of Tocilizumab for Coronavirus Disease 2019 (Covid-19) Patients: A Systematic Review and Meta-analysis - Hariyanto, Timotius Ivan; Hardyson, Willie; Kurniawan, Andree (Drug Research, 2021)
Background Currently, the data regarding the effectiveness and safety of tocilizumab as treatment for COVID-19 infection is still conflicting. This study aims to give clear evidence regarding the potential benefit and safety of tocilizumab in improving the outcome of COVID-19 patients.Methods We systematically searched the PubMed and Europe PMC database using specific keywords related to our aims until November 1st, 2020. All articles published on COVID-19 and tocilizumab were retrieved. Statistical analysis was done using Review Manager 5.4 software.Results A total of 38 studies with a total of 13 412 COVID-19 patients were included in our analysis. Our meta-analysis showed that tocilizumab treatment is associated with reduction of mortality rate from COVID-19 [OR 0.54 (95% CI 0.42–0.71), p<0.00001, I2=79%, random-effect modelling], but did not alter the severity of COVID-19 [OR 1.05 (95% CI 0.92–1.20), p=0.47, I2=84%, random-effect modelling] and length of hospital stay [Mean Difference 1.77 days (95% CI −0.61–4.14 days), p=0.15, I2=97%, random-effect modelling]. Tocilizumab also does not associated with serious adverse events compared with standard of care treatment [OR 0.91 (95% CI 0.71–1.15), p=0.42, I2=46%, random-effect modelling].Conclusion Our study does not support the routine use of tocilizumab for COVID-19 patients. Future studies should focus more on other potential therapies for COVID-19 patients.
Keywords: coronavirus disease 2019; COVID-19; tocilizumab; immunomodulator; treatment